Investigation of inertial cavitation threshold and corresponding thermal and mechanical effects using multi-frequency ultrasound signals in viscoelastic medium - Tatiana Filonets; Maxim Solovchuk; Chi-Fang Chen (Ultrasonics Sonochemistry, 2025)
This study numerically investigates the inertial cavitation threshold and the corresponding thermal and mechanical effects under multi-frequency (dual- and triple-frequency) ultrasonic signals. The Gilmore model, coupled with linear viscoelastic models, is used to simulate the bubble dynamics in different media. The inertial cavitation threshold is calculated for different initial bubble radii and various multi-frequency combinations, using two criteria: one based on the bubble radius expansion and the other based on the bubble collapse speed. The threshold results are analyzed, and the optimal frequencies are identified that yield the lowest possible threshold pressure across all studied initial bubble radii (the optimal threshold pressure). The optimal dual-frequency signal provides lower threshold pressures than a single-frequency signal, and the optimal triple-frequency signal further reduces the threshold pressure. Thresholds for the bubble collapse speed criterion are higher than for the radius criterion. Besides thresholds, power deposition (viscous and radiation power) and mechanical damage (strain-related damage) caused by cavitation are numerically investigated. For the bubble collapse speed criteria, the power values increases very rapidly (by about four orders of magnitude) when acoustic pressure is approximately equal to the estimated threshold pressure. For the radius criteria, a gradual increase of power deposition values is observed. The computation of strain is used to estimate a theoretical damage radius caused by tissue deformation during cavitation. Using the optimal frequencies for the bubble collapse speed criterion can lead to a significant enlargement of the strain-related damaged region compared to the radius criterion, with the enlargement factor reaching 20–30 times. Moreover, the damaged area significantly increases with the optimal triple-frequency signals compared to the optimal dual-frequency signals. The results presented in this study can be useful for further research on inertial cavitation and its effects in different media, as well as for focused ultrasound cancer treatments.